Performance of Dowelled Mortise and Tenon for Tropical Timber Species under Shear Load Test - Hassan, Rohana; Sidek, Muhd Norhasri Muhd; Hamid, Nor Hayati Abdul; Salit, Mohd Sapuan (Novel Perspectives of Engineering Research Vol. 9, 2022)
An experimental investigation of single-dowelled mortise and tenon was conducted using the European Yield Models (EYM) approach. Specimens were axially loaded in shear with structural size mortise and tenon dowelled with 20.6 mm diameter. Steel, glass fibre reinforced plastic (GFRP), and wood are used as test variables for the dowels. As the variables were adjusted, connections were tested until they failed to observe the final capacity and various ways of failure. The findings demonstrate thatthe shear strength capacity of the mortise and tenon connection single-dowelled with steel, GFRP, and wood is not directly reflect the capacity of the dowel. Steel, wood, and GFRP have the highest proportional limit, 5 percent diameter offset, and maximum connection strength, but steel, GFRP, and wood have the highest dowel yield modes. When compared to wood, GFRP failure modes were found to be as stiff as steel (mode Im) (mode IIIs).